La comunidad de peces de la Laguna de Términos: estructura actual comparada - Ayala-Pérez, Luis Amado; Ramos Miranda, Julia; Flores Hernández, Domingo (Revista de Biología Tropical, 2003)
The structure of the fish community in Terminos Lagoon, Campeche, is analyzed on the base the description of the abundance, distribution, length composition and identification of the dominant species. The results are discussed and compared with the published information. 437 trawl tows were made in 19 monthly collection in 23 sites between September 1997 to March 1999. A total of 25 588 individual with a total weight of 601.5 kg were grouped in 107 species, 76 gender and 37 families. The abundance of the fish community showed the following intervals in temporal scale: 0.395 to 0.895 ind/m2; 8.637 to 18.316 g/m2 and 18.358 to 34.837 g/ind. The Shannon index oscillated between 1.875 and 3.995 and 4.94 and 7.88 respectively. 18 dominant species were identified. The most important species by its numerical abundance and appearance frequency is Arius melanopus that represents to the 26.5% of the total catch followed by Diapterus rhombeus with 18.9%. As dominant species, Bairdiella chrysura, B. ronchus, Archosargus rhomboidalis, Eugerres plumieri, Cynoscion arenarius and Chaetodipterus faber, are fishing resources with local and regional value.